2011
DOI: 10.1002/ep.10611
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of reduced‐order neural network model based on proper orthogonal decomposition for BOD5 monitoring: Active and online prediction

Abstract: This study aims at providing a reduced‐order neural network model (RONNM) based on proper orthogonal decomposition (POD) for online prediction of the 5 days biochemical oxygen demand (BOD5). To achieve this goal, the POD method is used to reduce the input vectors to neural network (NN) model. Evaluation of the selected RONNM and its comparison with the model fed with all input vectors (NN model) shows that it reduces not only the output error but also computational cost. Results depict that Pearson correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…In order to improve models performance, the PCA technique was applied for data preprocessing. PCA seeks relevant directions for the input data that maximize variance [15].…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve models performance, the PCA technique was applied for data preprocessing. PCA seeks relevant directions for the input data that maximize variance [15].…”
Section: Resultsmentioning
confidence: 99%
“…The NN and RONN models had been developed for the Sefidrood River Basin drained by the Sefidrood River and located in the northwest of Iran (Figure 1). As mentioned in Noori et al's [21] study, the dataset which was used to develop NN and RONN models was collected from 132 water quality monitoring stations along Sefidrood River and its reaches in spring, summer, autumn and winter seasons. The main branch of the Sefidrood River originates from the Zagros Mountains and flows down to the south of Caspian Sea.…”
Section: Methodsmentioning
confidence: 99%
“…Onkal-Engin et al [14] developed a relationship between sewage odor and BOD by NN model and reported that NN model can be used to classify the sewage samples collected from deferent 2013 American Institute of Chemical Engineers locations of a wastewater treatment plant. Because of the prediction capability of NN techniques strongly depends on the number of input vectors, Noori et al [21] suggested proper orthogonal decomposition (POD) method to reduce the input vector to NN model for BOD 5 prediction in the Sefidrood River Basin. Dogan et al [16] compared NN and multilinear regression models to estimate daily BOD in the inlet of wastewater biochemical treatment plants and suggested that NN model could be employed successfully in estimating the daily BOD in the inlet of wastewater biochemical treatment plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walton et al and Xiao et al proposed a NIROM using radial basis function (RBF) method and proper othogonal decomposition (POD) [28,29]. Noack [30] and Noori [31] used neural network to construct a NIROM. Xiao et.…”
Section: Introductionmentioning
confidence: 99%